Representation of Class Conflict and Alienation of Characters in the Novel Qolbu Al-Lail by Naguib Mahfouz - Nisa’, Auliyah Khoirun (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to reveal the representation of class conflict and the phenomenon of character alienation in Naguib Mahfouz's novel Qalbu al-Lail. Through the perspective of Alan Swingewood's sociology of literature, this study dissects how discriminatory social structures suppress individual autonomy. The method used is descriptive qualitative with content analysis techniques. The results showed that: (1) Class conflict is manifested through the opposition between aristocratic values represented by the grandfather figure and the main character's life choices that clash with caste boundaries; (2) Character alienation occurs as a sociological consequence when the main character loses social status and inheritance rights, which causes him to be alienated from his original environment and himself; and (3) This novel reflects Mahfouz's critical view of the strict social stratification in Egypt that closes the space for individual freedom. The conclusion confirms that alienation in this novel is a direct product of rigid social structural pressure.